HAMBATAN KOMUNIKASI ANTAR BUDAYA DALAM FILM - Dyah Retno Pratiwi; Rahmat Wisudawanto (Universitas Kristen Satya Wacana, 2015)
Intercultural communication activity would certainly not be separated from the cultural barriers that exist therein. This is due to the difference of values embraced by both cultures that mutually contact each other. This research aims to analyze how communication barriers between cultures is happening between Anna character that comes from the United Kingdom and King Mongkut's as well as the people that came from Thailand using the film Anna and The King as its object. Scenes in the film will be analyzed in qualitative descriptive. The results of the analysis showed that the communication barriers between cultures that happened to include the resistance barriers of perception, verbal and non verbal barriers. Keywords: Film, communication barriers between cultures